Behavior of indented sandwiches structure with Nomex honeycomb core and metallic skins subjected to compressive loading (CAI) - Aminanda, Yulfian; Castanie, Bruno; Barrau, Jean-Jacques (Trans Tech Publication Inc., 2007)
A finite element model is proposed to determine the residual strength and the evolution of damage area of indented sandwiches structures with Nomex honeycomb core and metallic skins indented by a spherical indenter under longitudinal compression load (CAI). The honeycomb is represented by a grid of non-linear springs which its behavior law is obtained by performing simple transverse uniform compression test on a block of honeycomb alone.The comparisons between computation and test result show that the model can simulate accurately the form of damage geometry during indentation, its residual print when the load is relieved (relaxation) and the residual strength and the evolution of damage geometry during CAI.